2017
DOI: 10.1049/el.2016.4025
|View full text |Cite
|
Sign up to set email alerts
|

Si waveguide polarisation rotation chirped Bragg grating

Abstract: Polarisation independent silicon waveguide wavelength filter using Bragg grating with chirped period is reported. The polarisation rotation and filter peak with wide flat top response is obtained. An antisymmetric grating structure and rib waveguide is used. We experimentally obtained polarisation independent flat-top band-pass filter consisting of polarisation beam splitter (PBS) and Bragg grating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The problem of narrow stop band can be overcome by using chirped grating. 33) We also showed theoretically that a flat-top response can be obtained by a two cavity structure. The features of devices described in Sects.…”
Section: Discussionmentioning
confidence: 71%
“…The problem of narrow stop band can be overcome by using chirped grating. 33) We also showed theoretically that a flat-top response can be obtained by a two cavity structure. The features of devices described in Sects.…”
Section: Discussionmentioning
confidence: 71%
“…[20][21][22][23][24][25][26][27] We reported experimental polarization rotation Bragg grating devices using a waveguide with nonvertical side wall, rib waveguide, and terrace corrugation structures. We showed that many types of polarization rotating grating structures such as sampled grating, superstructure, chirped period, and cavity incorporated devices [28][29][30][31][32] can possibly be obtained.…”
Section: Introductionmentioning
confidence: 99%